A meta‐analysis of perfusion parameters affecting weight gain in ex vivo perfusion - Marlar, Riley; Abbas, Fuad; Obeid, Rommy; Frisbie, Sean; Ghazoul, Adam; Rezaee, Ava; Sims, Jack; Rampazzo, Antonio; Bassiri Gharb, Bahar (Artificial organs, 2025)
Background Ex vivo machine perfusion (EVMP) has been established to extend viability of donor organs. However, EVMP protocols are inconsistent. We hypothesize that there is a significant relationship between specific parameters during EVMP and perfusion outcomes. Methods A meta‐analysis of literature was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) Statement. The search encompassed articles published before July 25, 2023. PubMed, Embase, and CENTRAL databases were screened using search terms “ex‐vivo,” “ex‐situ,” “machine,” and “perfusion.” Weight gain, an indicator of organ viability, was chosen to compare outcomes. Extracted variables included perfused organ, warm and cold ischemia time before perfusion, perfusion duration, perfusate flow, pressure, temperature, perfusate composition (presence of cellular or acellular oxygen carrier, colloids, and other supplements) and percent weight change. Data were analyzed using SPSS statistical software. Results Overall, 44 articles were included. Red blood cell‐based perfusates resulted in significantly lower weight gain compared to acellular perfusates without oxygen carriers (11.3% vs. 27.0%, p < 0.001). Hemoglobin‐based oxygen carriers resulted in significantly lower weight gain compared to acellular perfusates (16.5% vs. 27%, p = 0.006). Normothermic perfusion led to the least weight gain (14.6%), significantly different from hypothermic (24.3%) and subnormothermic (25.0%) conditions (p < 0.001), with no significant difference between hypothermic and subnormothermic groups (24.3% vs. 25.0%, p = 0.952). There was a positive correlation between flow rate and weight gain (ß = 13.1, R = 0.390, p < 0.001). Conclusions Oxygen carriers, low flow rates, and normothermic perfusate temperature appear to improve outcomes in EVMP. These findings offer opportunities for improving organ transplantation outcomes. Oxygen carriers, lower flow rates, and normothermic perfusate temperature appear to improve outcomes in ex vivo machine perfusion.